RUNX1-mutated families show phenotype heterogeneity and a somatic mutation profile unique to germline predisposed AML - Brown, Anna L.; Bochtler, Tilmann; Fröhling, Stefan (Blood advances, 2020)
Key Points. Germline RUNX1 mutations lead to significant phenotypic heterogeneity in families.Germline RUNX1-mutated acute myeloid leukemia has a different som
Gesehen am 23.04.2020